Molecular markers for artemisinin and partner drug resistance in natural Plasmodium falciparum populations following increased insecticide treated net coverage along the slope of mount Cameroon: cross-sectional study - Apinjoh, T; Mugri, R; Miotto, O; Chi, H; Tata, R; Anchang-Kimbi, J; Fon, E; Tangoh, D; Nyingchu, R; Jacob, C; Amato, R; Djimde, A; et al. (BioMed Central, 2017)
Background Drug resistance is one of the greatest challenges of malaria control programmes, with the monitoring of parasite resistance to artemisinins or to Artemisinin Combination Therapy (ACT) partner drugs critical for elimination efforts. Markers of resistance to a wide panel of antimalarials were assessed in natural parasite populations from southwestern Cameroon. Methods Individuals with asymptomatic parasitaemia or uncomplicated malaria were enrolled through cross-sectional surveys from May 2013 to March 2014 along the slope of mount Cameroon. P. falciparum malaria parasitaemic blood screened by light microscopy was depleted of leucocytes using CF11 cellulose columns and the parasite genotype ascertained by sequencing on the Illumina HiSeq platform. Results A total of 259 participants were enrolled in this study from three different altitudes. While some alleles associated with drug resistance in pfdhfr, pfmdr1 and pfcrt were highly prevalent, less than 3% of all samples carried mutations in the pfkelch13 gene, none of which were amongst those associated with slow artemisinin parasite clearance rates in Southeast Asia. The most prevalent pfcrt, pfmdr1, pfdhfr and pfdhps haplotypes were triple mutants for pfcrt-74, 75, and 76 i.e. C72V73I74E75T76 (47.3%), a single mutation at codon 184, N86F184D1246 (53.2%), the I51R59N108I164 (99%) and S436G437K540A581A613 (69%) variants in the genes respectively. Conclusions The predominance of the pfcrt CVIET and dhfr IRN triple mutant parasites and absence of pfkelch13 resistance alleles suggest that the amodiaquine and pyrimethamine components of AS-AQ and SP may no longer be effective in their role while chloroquine resistance still persists in southwestern Cameroon.